Targeted endothelial gene deletion of triggering receptor expressed on myeloid cells-1 protects mice during septic shock. Issue 6 (19th January 2018) - Jolly, Lucie; Carrasco, Kevin; Derive, Marc; Lemarié, Jérémie; Boufenzer, Amir; Gibot, Sébastien
Abstract: Aims: TREM-1 (Triggering Receptor Expressed on Myeloid cells-1) is an immunoreceptor expressed on neutrophils and monocytes/macrophages whose role is to amplify the inflammatory response driven by Toll-Like Receptors engagement. The pharmacological inhibition of TREM-1 confers protection in several pre-clinical models of acute inflammation. In this study, we aimed to decipher the role of TREM-1 on the endothelium. Methods and results: We first showed by qRT-PCR, flow cytometry and confocal microscopy that TREM-1 was expressed in human pulmonary microvascular endothelial cells as well as in mouse vasculature (aorta, mesenteric artery, and pulmonary vessels). TREM-1 expression was upregulated following septic insult. We next observed that TREM-1 engagement impaired mouse vascular reactivity and promoted vascular inflammation. The pharmacological inhibition of TREM-1 (using the synthetic inhibitory peptide LR12) prevented these disorders both in vitro and in vivo. We generated endothelium-conditional Trem-1 ko mice (EndoTREM-1 −/− ) and submitted them to a caecal ligation and puncture-induced septic shock. As compared with wild-type littermates, targeted endothelial Trem-1 deletion conferred protection during septic shock in modulating inflammatory cells mobilization and activation, in restoring vasoreactivity, and in improving the survival. Conclusion: We reported that TREM-1 is expressed and inducible in endothelial cells and plays a direct role in vascular inflammation and dysfunction. The targeted deletion of endothelial Trem-1 conferred protection during septic shock in modulating inflammatory cells mobilization and activation, restoring vasoreactivity, and improving survival. The effect of TREM-1 on vascular tone, while impressive, deserves further investigations including the design of endothelium-specific TREM-1 inhibitors.